Changing Clinical Presentation, Current Knowledge-Attitude-Practice, and Current Vision Related Quality of Life in Self-Reported Type 2 Diabetes Patients with Retinopathy in Eastern India: The LVPEI Eye and Diabetes Study - Taraprasad Das; Batriti Wallang; Preeti Semwal; Soumyava Basu; Tapas R. Padhi; Mohd Hasnat Ali (Journal of Ophthalmology)
Purpose. To document the changing clinical presentation of diabetic retinopathy (DR) over a decade, the current knowledge-attitude-practice (KAP) of known type 2 diabetes mellitus (DM) patients, and the current vision related quality of life (VR-QOL) of patients with DR in a tertiary eye care center in Eastern India. Methods. Two hundred and forty patients with known type-2 DM were evaluated. The evaluation included status of DR (n=240), KAP (n=232), and VR-QOL (n=75). International classification of DR was used in the study. The DR status was compared with another cohort (n=472) examined a decade earlier, in year 2001. The KAP-25 questions were designed after literature review. The National Eye Institute Visual Function Questionnaire (NEI-VFQ; including optional items) was validated by Rasch analysis. Both KAP and VR-QOL were analyzed according to degree of DR, duration of known DM, and educational qualification. Results. Average age of the current cohort (n=240) was 57.16 ± 9.03 years; there were 205 (85.4%) male patients and 143 (59.6%) patients had received less than graduate qualification. The mean duration of DM since diagnosis was 10 ± 7.8 months (range 8 months to 30 years); 118 (49.16%) patients had DR. In a decade time, 2001 to 2011, there was a change of retinopathy status at presentation (more often nonproliferative diabetic retinopathy, NPDR). One-third of NPDR patients had poor vision and half of them were hypertensive. KAP was better in patients with higher education and those having DR. VFQ score was higher in better seeing patients. Conclusion. Patients currently presenting at earlier stage of retinopathy are probably related to poor vision. Early detection and treatment of DR is likely to preserve and/or improve vision.